2015
DOI: 10.1179/1743286315y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of coal-mine waste in solid backfill mining in China

Abstract: Recently, issues pertaining to surface disposal of coal-mine wastes, particularly environmental pollution, have been the focus of increasing national and international concern. Solid backfill mining (SBM) method provides environmentally, economically and technically acceptable solutions to these issues by, inter alia, significantly increasing waste-disposal capacities, improving resource recovery rates and reducing levels of ground deformation. In the current study, the physical and mechanical properties of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Linear Regression Analysis: H.F. Yan(2010) [4] used linear statistical rule and gas geology factor analysis method to determine the main control factors of Peigou mine coal seam gas content, and established the Peigou mine coal seam gas content prediction model with multiple linear regression analysis method. [6] found that the gas concentration prediction model between buried depth and gas content has the problem that estimated values were lower than the actual, and proposed the corresponding monadic linear regression correction model. B.B.…”
Section: Regression Analysis Methodsmentioning
confidence: 99%
“…Linear Regression Analysis: H.F. Yan(2010) [4] used linear statistical rule and gas geology factor analysis method to determine the main control factors of Peigou mine coal seam gas content, and established the Peigou mine coal seam gas content prediction model with multiple linear regression analysis method. [6] found that the gas concentration prediction model between buried depth and gas content has the problem that estimated values were lower than the actual, and proposed the corresponding monadic linear regression correction model. B.B.…”
Section: Regression Analysis Methodsmentioning
confidence: 99%
“…Aimed at emancipating the coal resources and solving the problem of gangue accumulation on the ground surface, solid backfilling technology has been developed by backfilling solid waste like gangue into mined-out areas so as to effectively control strata movement and reduce surface deformation and ensure the safety of ground buildings [4][5][6][7][8]. Involved in the self-organization process of strata movement, the backfilling materials under roof pressure would undergo vertical compression and deformation [9][10][11][12]. Nevertheless, in the process of compression, the backfilling body would play an increasingly supportive role for the roof and hence share part of the overlying strata load.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the amount of coal mining waste (CMW) was 315 million tons for underground coal mining [3]. Therefore, the recycling of industrial wastes as construction materials has been interested in many countries to minimize the environmental impacts caused by the landfill area [4], as well as replacing the natural aggregates for the construction industry [3,[5][6][7][8][9][10][11][12]. Indranratna et.…”
Section: Introductionmentioning
confidence: 99%
“…CBR values of the specimens compacted at the OMC of 12% using the modified Proctor is 90%, which is much higher than that values achieved for standard Proctor specimens at similar moisture contents (only about 20%). H. Jang [9] also researched the characterization of seven coal-mine wastes in solid backfill mining in China. The results show that the MDD varied within the range 1.636-1.917 g/cm 3 , while OMC ranged from 6.64 to 11.03%.…”
Section: Introductionmentioning
confidence: 99%